2015
DOI: 10.1108/ijesm-08-2014-0003
|View full text |Cite
|
Sign up to set email alerts
|

Signaling with convertible debt in the renewable energy industry?

Abstract: Purpose – The purpose of this paper is to show how convertible debt is used in the renewable energy industry. The authors argue that there is an investor rationing component to the design and market impact of convertible debt securities. Design/methodology/approach – The authors apply event study methodology, option pricing theory and risk shift analysis to examine capital market reactions following the issuance of convertible debt by ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
(94 reference statements)
0
1
0
Order By: Relevance
“…Several previous studies were used as references in this research, such as the (1) Renewable energy by Kartal and Ömer (2016), Kong (2017), Gatzert and Kosub (2017), Kahla (2017), Ettenhuber and Dirk (2015), Alabi (2017), Kunert (2017), Ramana (2012), Mourshed and Mohammed (2009), Wang and Li (2009), Mohanty (2012), Singh (2012), Abdelhamid (2011), Mezher (2010), Cato (2008), Lacouture and Kathy (2009), Soni (2017), Pregger (2011), (2) Geothermal by Stritih (2015), Liu (2017), Bargh (2012), Al-Khoury (2010), Herrera (2010). No previous study has been found the new geothermal law and its implications for geothermal development, especially in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies were used as references in this research, such as the (1) Renewable energy by Kartal and Ömer (2016), Kong (2017), Gatzert and Kosub (2017), Kahla (2017), Ettenhuber and Dirk (2015), Alabi (2017), Kunert (2017), Ramana (2012), Mourshed and Mohammed (2009), Wang and Li (2009), Mohanty (2012), Singh (2012), Abdelhamid (2011), Mezher (2010), Cato (2008), Lacouture and Kathy (2009), Soni (2017), Pregger (2011), (2) Geothermal by Stritih (2015), Liu (2017), Bargh (2012), Al-Khoury (2010), Herrera (2010). No previous study has been found the new geothermal law and its implications for geothermal development, especially in Indonesia.…”
Section: Introductionmentioning
confidence: 99%